Study on the Influence Law of Temperature Profile of Vertical Wells in Gas Reservoirs - Hansong, Ma; Luo, Hongwen; Haitao, Li; Yuxing, Xiang; Qin, Zhang; Ying, Li (International Journal of Petroleum Technology, 2022)
Due to the lack of a robust temperature model and poor knowledge about the influence law of temperature profile, it is still highly challenging to interpret the production profile of vertical wells in layered gas reservoirs from distributed temperature sensing (DTS) quantitatively. In this paper, a coupled temperature prediction model for vertical wells in the layered gas reservoir is developed, considering several microthermal effects and non-isothermal seepage. Based on the theoretical simulation, several single factors’ influence on the vertical well’s temperature profile in a layered gas reservoir has been analyzed. The sensitivity of temperature profiles on different affecting factors has been evaluated through orthogonal test analysis. It has been found that the influence degree of each factor on the temperature profile of the vertical well in the layered gas reservoir is as follows: formation permeability > production rate >water saturation > wellbore inclination angle > relative density of natural gas > formation thermal conductivity > wellbore diameter (k >Qg > SW > θ > dg > Kt > D). The dominant factors affecting the temperature profile of vertical wells in layered gas reservoirs are formation permeability, production rate, and water saturation. The proposed temperature prediction model can serve as the forward model when developing the inversion system to interpret DTS measurement. The findings of this paper provide solid theoretical support for the quantitative interpretation of the flow rate profile for vertical wells in layered gas reservoirs.